Chronic myeloid leukemia and interferon-α: a study of complete cytogenetic responders - Bonifazi, Francesca; Vivo, Antonio de; Rosti, Gianantonio; Guilhot, François; Guilhot, Joëlle; Trabacchi, Elena; Hehlmann, Rüdiger; Hochhaus, Andreas; Shepherd, Patricia C. A.; Steegmann, Juan Luis; Kluin-Nelemans, Hanneke C.; Thaler, Josef; et al. (Blood, 2001)
Achieving a complete cytogenetic response (CCgR) is a major target in the treatment of chronic myeloid leukemia (CML) with interferon-α (IFN-α), but CCgRs are rare. The mean CCgR rate is 13%, in a range of 5% to 33%. A collaborative study of 9 European Union countries has led to the collection of data on 317 patients who were first seen between 1983 and 1997 and achieved CCgRs with IFN-α alone or in combination with hydroxyurea. The median time to first CCgR was 19 months (95% CI, 17-21; range, 3-84 months). At last contact, 212 patients were still alive and in continuous CCgR; 105 patients had lost CCgR, but 53% of them were still alive and in chronic phase. IFN-α treatment was discontinued permanently in 23 cases for response loss, in 36 cases for chronic toxicity (15 are still in unmaintained continuous CCgR), and in 8 cases because it was believed that treatment was no longer necessary (7 of these 8 patients are still in unmaintained continuous CCgR). The 10-year survival rate from first CCgR is 72% (95% CI, 62%-82%) and is related to the risk profile. High-risk patients lost CCgR more frequently and more rapidly and none survived more than 10 years. Low-risk patients survived much longer (10-year survival probability 89% for Sokal low risk and 81% for Euro low risk). These data point out that a substantial long-term survival in CCgRs is restricted mainly to low-risk and possibly intermediate-risk patients and occurs significantly less often in high-risk patients.